DETEKSI CEKAMAN OKSIDATIF AKIBAT TOKSISITAS KROM PADASonchus oleraceus L. MELALUI PENENTUAN SPESIES OKSIGEN REAKTIF SECARA SPEKTROFOTOMETRI DAN HISTOKIMIA - Sri Kasmiyati; - Sucahyo (Agric, 2014)
Increased production of reactive oxygen species or ROS is one of the common responses to a wide range of biotic and abiotic stresses. Increased production of ROS is outstripping endogenous antioxidant defense systems has been referred to as oxidative stress. Heavy metals are known to initiate ROS generation which is implicated as a oxidative stress. Cr is a toxic heavy metal that can generate ROS like H2O2 and O2 - which cause oxidative stress. In this study, chromium toxicity was studied to detect the oxidative stress on Sonchus oleraceus weed plants by the detection of superoxide anion and H2O2. Superoxide anion was detected by staining techniques with nitroblue tetrazolium (NBT) and hydrogen peroxide by Diaminobenzidine tetrahydrochloride (DAB) staining. Results indicated that the plants were grown in sand media generate the highest (0.89 A/g FW and 3.23 mol/g FW) than in soil media (0.23 A/g FW and 2.11 mol/g FW) superoxide anion (*O- 2) and H2O2 and soil containing textile sludge (0.18 A/g FW and 2.66 mol/g FW), respectively. At application of 10 mg Cr6+/L and 250 mg Cr3+/L, the production of *O- 2 and H2O2 in leaves of sonchus plants were significantly increased compared with the control plants. The highest production of H2O2 and *O- 2 were showed in the leaves of sonchus plants grown in sand media with Cr6+ application. In this study, either Cr3+ or Cr6+ caused oxidative stress in Sonchus oleraceus weed plants. The result also showed that sonchus plants esposed to toxic Cr can suffer from oxidative stress leading to reduction of its fresh and dry plants biomass. NBT and DAB in an appropriate probe and significant value for monitoring the formation of *O- 2 and H2O2 in plants.